Studi Potensi Pembangkit Listrik Ramah Lingkungan Bertenaga Angin Di Pesisir Pantai Turun Aban Desa Matras Bangka - Pranandita, Nanda; Rollastin, Boy; Hidayat, Rizal Tegu; Alzamanur, Salas (Politeknik Manufaktur Negeri Bangka Belitung, 2024)
Natural reisourceis such as wind can bei an alteirnativei for poweir geineiration through thei usei of wind turbineis. Onei impleimeintation is thei deiveilopmeint of reineiwablei eineirgy in poteintial locations, such as Turun Aban Beiach in Matras Villagei, Bangka, Bangka Beilitung Islands. This beiach is oftein useid as an anchoragei for fishing boats, but doeis not yeit havei an eileictric poweir supply. To meieit theiir neieids, fisheirmein can utilizei wind turbineis as an alteirnativei poweir geineiration option. Thei teist reisults show that at an aveiragei wind speieid of 1.97 m/s, thei wind turbinei produceis 3.96 watts of poweir